A new inversion algorithm (PyMDS) based on the Pyro library to use chlorine 36 data as a paleoseismological tool on normal fault scarps - Llinares, Maureen; Gassier, Ghislain; Viseur, Sophie; Benedetti, Lucilla (Applied computing and geosciences, 2025)
Paleoseismology (study of earthquakes that occurred before records were kept and before instruments can record them) provides useful information such as recurrence periods and slip rate to assess seismic hazard and better understand fault mechanisms. Chlorine 36 is one of the paleoseismological tools that can be used to date scarp exhumation associated with earthquakes events. We propose an algorithm, PyMDS, that uses chlorine 36 data sampled on a fault scarp to retrieve seismic sequences (age and slip associated to each earthquake) and long term slip rate on a normal fault. We show that the algorithm, based on Hamiltonian kernels, can successfully retrieve earthquakes and long term slip rate on a synthetic dataset. The precision on the ages can vary between few thousand years for old earthquakes (>5000 yr BP) and down to few hundreds of years for the most recent ones (<2000 yr BP). The resolution on the slip is ∼30–50 cm and on the slip rate is ∼ 1 mm/yr. Diagnostic tools (Rhat and divergences on chains) are used to check the convergence of the results. Our new code is applied to a site in Central Italy, the results yielded are in agreement with the ones obtained previously with another inversion procedure. We found 4 events 7800±400 yr, 4700±400 yr, 3000±200 and 400 ±20 yr BP on the MA3 site. The associated slips were of 130±10 cm, 140±20 cm, 580 ± 20 cm and 205±20 cm. The results are comparable with a previous study made by (Schlagenhauf et al., 2010). The yielded slip rate of 2.7 mm/yr ± 0.4 mm/yr is also coherent with the one determined by Tesson et al. (2020). •PyMDS inverts 36Cl dataset using HMC methods with diagnostic tools for a better assessment of the results.•PyMDS allows easy integration of a-priori from other methods (paleoseismological trenches or fault plane roughness analysis)•Usage of Python makes PyMDS user friendly and easy to install.